Personal style bloggers: the most popular visual composition principles and themes on instagram - Ramos-Serrano,Marina (2016)
Instagram is one of the main social networking services personal style bloggers choose for interacting with followers. The goal of the present study is to detect the most common principles of visual composition and themes used by the worlds ten most influential bloggers. To achieve this goal we have employed a content analysis, using a sample of 503 Instagram images. The results indicate that the bloggers visual pattern of choice on Instagram corresponds to a wide shot with a full body view of the blogger against a significant background. The shot is taken at eye level angle and the predominant visual elements -the blogger and/or the product- are located in the centre of the photograph.